PROBLEMS OF LABOUR FORCE CUSTOMIZATION IN A MEGALOPOLIS - O. A. Tettsoeva (Вестник университета)
Shortage of labour force implies making more efficient use of the existing labor potential in a megalopolis. It puts in question the determination of the actual deficiency of workforce. This predetermines the need to study the problems associated with the identification and analysis of factors in the formation of the labour market. The functioning of manpower market is affected by a range of factors relating to the formation of the labour force additional reserve groups. Increasing migration flows requires solving the issues of optimizing their volumes. In our view, it is necessary to separate the problem of improving the demographic situation in a metropolis due to migration processes, on the one hand, from using of migration as a key source of covering a mega-city economy’s need for labour force, on the other hand. The issues of the workforce customization in a metropolis are becoming obligate. Thus, the regulation of the availability of the mega-city economy in the labour force implies, on the one hand, analysis and identification of reserve groups of labour resources and, on the other – the customization of the product “labour force” for the needs of a specific consumer.